Optimal tuning of virtual inertia control for frequency regulation of microgrid - Fadheel, Bashar Abbas; Abdul Wahab, Noor Izzri; Mahdi, Ali Jafer; Mohd Radzi, Mohd Amran; Che Soh, Azura; Mohammed Ridha, Hussein; Veerasamy, Veerapandiyan (IEEE Canada, 2024)
The integration of renewable energy sources in modern microgrid power systems has a significant impact on frequency stability due to reducing inertia and damping coefficient. This article employs a virtual inertia control (VIC) based on frequency deviation derivatives to emulate the system inertia and damping coefficient characteristics of traditional synchronous generators. Coordination between the global controller (load frequency control) and the VIC is implemented. The parameters of both the secondary and virtual control are tuned using a novel hybrid sparrow search algorithm with mountain gazelle optimizer algorithm. The simulation results demonstrate a substantial improvement in mitigating the low inertia of the power system when exposed to consecutive rapid load changes, utilizing the suggested algorithm on comparing with the hybrid sparrow search algorithm based on grey wolf optimizer. © 2021 IEEE.